Proceedings of the workshop on information technology tools for natural disaster risk management, February 04-06, 1998, AIT, Thailand - Herath, Srikantha (International Center for Disaster-Mitigation Engineering, Institute of Industrial Science, University of Tokyo, 1999)
"Information Technology Tools for Natural Disaster Risk Management" is a timely compilation of selected reviewed papers presented at the international workshop held under the same title in Asian Institute of Technology, Bangkok, Thailand in 1998. The workshop brought together researchers, engineers, and scientists working with information technology tools ranging from GIS, remote sensing, communication networks and database applications for natural disaster risk reduction to exchange ideas and experiences. The volume details applications in floods, earthquakes, risk assessment, disaster monitoring and response, data management and role of information technologies in disaster management focusing on Asia Pacific Region. It also provides a host of information on the vast range of possibilities available for natural disaster risk management in emerging technologies.